Development of Tourism along the Silk Road - Safarova , Marjona (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2025)
The Silk Road, historically known as the ancient trade route connecting the East and the West, has become a central focus for international tourism development in the twenty-first century. This paper explores the significance of the Silk Road as a cultural and economic bridge, with particular emphasis on Uzbekistan’s role as a geographical and historical center of the route. It examines the potential of Silk Road tourism for fostering intercultural dialogue, regional cooperation, and economic growth. Furthermore, the study identifies existing challenges and proposes strategies for sustainable development of tourism along this historic corridor.